Numerical and experimental investigations on a bladeless turbine: Tesla's cohesion-type innovation - Malayathi Sivaramakrishnaiah; Dhanaraj Savary Nasan; Prabhakar Sharma; Thanh Tuan Le; Minh Ho Tran; Thi Bich Ngoc Nguyen; Phuoc Quy Phong Nguyen; Viet Dung Tran (International Journal of Renewable Energy Development, 2024)
The design, numerical simulation, manufacturing, and physical experimentation of Tesla's bladeless centripetal turbine for electrical power production are the topics of this research project. The turbine generates rotational motion in the discs by directing pressurized air and water tangentially across parallel smooth disc surfaces. The fluid speed parameter at the nozzle inlet determines the power generated. To ensure optimal mechanical design parameters, SolidWorks design software, fluid dynamics concepts, and machine element design were employed. The numerical simulation software ANSYS CFX was used. The numerical and qualitative findings of the models and physical experiments coincided well. The study revealed that the power production and turbine efficiency were regulated by the input sources and blade size. Variations in the fluid composition between the discs may additionally have an impact on the outcomes. The researchers investigated the connection between input fluid pressure and turbine efficiency, as well as the number of discs and turbine power. The prototype could generate 76.52 W of electricity at 50 bar pressure and 1.01e+05 Reynolds number. The operation was efficiently simulated using CFD, with only a 9.3% difference between experimental and simulated results. Overall, this research provides an in-depth assessment of Tesla's bladeless centripetal turbine. It verifies the design and numerical simulation methodologies used, as well as identifies the essential aspects impacting turbine performance and efficiency. The findings contribute to a better understanding of the turbine's behavior and give ideas for improving its performance.